ЛІБЕРАЛІЗАЦІЯ СТАБІЛІЗАЦІЙНОЇ МАКРОЕКОНОМІЧНОЇ ПОЛІТИКИ: ДОСВІД ШВЕЦІЇ ТА УРОКИ ДЛЯ УКРАЇНИ - R. Kalinovskyi (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)

(untitled)
Annotation. The article examines the causes and prerequisites of economic growth in Sweden after a long crisis of 1980-90-ies. The essence of the process of development and implementation of the stabilization macroeconomic policy in Sweden on the way to achieving sustainable economic development is considered. The Swedish government and Central Bank stabilization tools using is investigated. The recommendations to improve the economic environment in Ukraine are developed.